Analisis Pemetaan Bibliometrik Komputational Publikasi Pada “Ergonomics”, “Human Factor” dan “Occupational Health” dengan Menggunakan VOSviewer - Ario Wicaksono; Indri Hapsari Susilowati; Afifah Mu'minah (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2026)
Ergonomics, Human Factor, and Occupational Health are crucial interrelated disciplines for optimizing human interaction within work systems. Bibliometric analysis offers a quantitative approach to map the development and intellectual structure of these fields. This study aims to conduct a computational bibliometric mapping analysis of scientific publications related to "Ergonomics", "Human Factor", and "Occupational Health" to identify research structures, developmental trends, and potential areas for future research. Publication data from 2014-2024 (comprising 536 articles) were retrieved from the Scopus database and analyzed using Publish or Perish software for data extraction and VOSviewer software for keyword co-occurrence analysis, clustering, and visualization. The analysis identified publication trends and mapped the research landscape into 6 major thematic clusters, showcasing interconnections and the evolution of topics within the three fields. Network, density, and overlay visualizations were used to present these findings. This study provides comprehensive insights into current research dynamics and identifies potential focus areas for future research in Ergonomics, Human Factor, and Occupational Health.